Essential role of AT1A receptor in the development of 2K1C hypertension - Cervenka, Ludek; Horácek, Vladislav; Vanecková, Ivana; Hubácek, Jaroslav A; Oliverio, Michael I; Coffman, Thomas M; Navar, L Gabriel (Hypertension (Dallas, Tex., 2002)
The aims of this study were to delineate the relative contribution of angiotensin II (ANG II) subtype 1A (AT1A) and 1B (AT1B) receptors to the development of two-kidney, one-clip (2K1C) Goldblatt hypertension in mice, to examine if increased nitric oxide synthase (NOS) activity counteracts the vasoconstrictor influences of ANG II in 2K1C hypertensive mice, and to determine the role of ANG II type 2 (AT2) receptors in 2K1C hypertension in mice. AT(1A) ANG II receptor knockout (AT1A-/-) and wild-type (AT1A+/+) mice underwent clipping of the right renal artery. Systolic blood pressure (SBP) was significantly lower in AT1A-/- compared with AT1A+/+ mice, and neither clip placement nor AT2 receptor blockade with PD 123319 (PD) altered SBP in AT1A-/- mice. A significant and sustained rise in SBP from 119+/-5 to 163+/-6 mm Hg was observed in the 2K1C AT1A+/+ mice from day 10 to day 26. Chronic PD infusion did not alter the course of hypertension in 2K1C/AT1A+/+. Acute PD infusion did not alter mean arterial pressure (MAP) in AT1A+/+, PD/AT1A+/+, 2K1C/AT1A+/+, PD/2K1C/AT1A+/+, AT1A-/-, PD/AT1A-/-, and PD/2K1C/AT1A-/- mice compared with basal levels. In contrast, acute PD infusion caused significant increases in MAP in 2K1C/AT1A-/- mice. The subsequent acute NOS inhibition caused greater increases in MAP in 2K1C/AT1A+/+ and PD/2K1C/AT1A+/+ mice than in AT1A+/+ and PD/AT1A+/+ mice. These results support the essential role of AT1A receptors in mediating 2K1C hypertension and support the hypothesis that augmented NO production serves as a counteracting system in this model of hypertension.
Keywords: Imidazoles; velikost orgánu; modely nemocí na zvířatech; Receptors, Angiotensin; Male; Mice, Knockout; imidazoly; Organ Size; progrese nemoci; antagonisté receptorů pro angiotenzin; Receptor, Angiotensin, Type 1; Myocardium; receptor angiotensinu typ 1; Kidney; receptory angiotensinu; mužské pohlaví; Disease Progression; Enzyme Inhibitors; renovaskulární hypertenze; Receptor, Angiotensin, Type 2; receptor angiotensinu typ 2; Body Weight; myši knockoutované; Animals; krevní tlak; ledviny; zvířata; Angiotensin Receptor Antagonists; synthasa oxidu dusnatého; Nitric Oxide Synthase; pyridiny; Blood Pressure; Disease Models, Animal; myši; Hypertension, Renovascular; Pyridines; Mice; tělesná hmotnost; inhibitory enzymů; myokard